SOCIAL DIMENSION OF SLANG WORD IN FILM “ANIMAL KINGDOM” - euis - meinawati (LPPM Universitas Bina Sarana Informatika, 2017)
The research is aimed at finding out the social dimension of slang words which is uttered in film Animal Kingdom. The writer uses film as the main medium to analyze the construction of social dimension in slang utterance. The method of this study is descriptive content analysis. Data were collected with pursued based on unit analysis, identification, coding, and classification. The procedure of data analysis and interpretation adapted pattern made by Phillip Myring.. Some problems will be analyzed in this thesis are the social factors and social dimension can influence the use of slang. In this analysis, the writer finds that slang usually used in an informal situation and in the certain social class of society. The use of slang relates with social factors that consist of the participant, setting, topic, and function meanwhile social dimension affected it in social distance scale, status scale, formality scale, and two functional scales.